FRI0014 Il-21 is upregulated in sle and promotes tfh-mediated b cell maturation and ig production. (23rd January 2014) - Cox, J. H.; Hussell, S. W.; Thomas, E. P.; Wu, R.; Valliant-Saunders, K.; Smith, P.; Peng, S. L.; Blumberg, H.; Levin, S. D.; Lundsgaard, D.
Abstract : Background: The dysregulation of germinal centers and ectopic follicles, resulting in hyperactive B cells, is thought to be a key mechanism leading to systemic lupus erythematosus (SLE). Interleukin-21 (IL-21) is a pro-inflammatory cytokine that is proposed to contribute to the pathogenesis of several autoimmune inflammatory disorders, including SLE. In mice, IL-21 is described as a regulator of T follicular helper (Tfh) cell differentiation and B cell maturation. However, there is limited published data evaluating the function of IL-21 in the human immune system or the relevance of IL-21 in SLE. Objectives: In the present study, our aim was to investigate IL-21 and IL-21 receptor (IL-21R) expression in SLE and the role of the IL-21 pathway in germinal center biology. Methods: We obtained peripheral blood from patients with active SLE (SLEDAI ≥4) and age/gender-matched healthy controls. Patients had been treated with less than 20 mg/day Prednisone and had not received B cell depleting therapy. Expression of IL-21 and IL-21R was analysed by flow cytometry or RT-PCR. For functional studies, Tfh and B cells were sorted from tonsils or peripheral blood from healthy individuals, stimulated with SEB, and proliferation and Ig production were measured by CFSE dilution and luminex, respectively. Results: In the periphery, IL-21 was produced by CD4 + and CD8 + cells, and IL-21 levels were significantly higher in SLE CD4 + cells compared to healthy controls as measured by intracellular cytokine staining. Furthermore, increased levels of IL-21 correlated with elevated IL-17 and IFN-γ production. IL-21R was expressed on CD4 + T cells, CD8 + T cells, NK cells, B cells, and mature DCs, and levels were not significantly altered in SLE samples. CD4 + Tfh cells from human tonsils or peripheral blood produced significantly more IL-21 than non-Tfh cells and blockade with a neutralising anti-IL-21 antibody resulted in a moderate decrease in Tfh proliferation. In Tfh-B cell co-culture assays from either tonsils or peripheral blood, anti-IL-21 inhibited B cell maturation, as measured by Ig production. Conclusions: Together, these data demonstrate elevated IL-21 production in SLE patients and provide evidence for an IL-21 mediated effect on Tfh proliferation and Tfh-induced B cell maturation in humans. Therefore, targeting IL-21 activity with a neutralising antibody has potential as a novel therapeutic approach for the treatment of autoimmune inflammatory disorders such as SLE. Acknowledgements: We acknowledge Dr. Jane Buckner, Melissa Peda, Gina Marchesini, Kevin Criste, Christine Chan, and Thien-Son Nguyen from the Benaroya Research Institute at Virginia Mason for their contributions to these studies. Disclosure of Interest: J. Cox Employee of: Novo Nordisk, S. Hussell Employee of: Novo Nordisk, E. Thomas Employee of: Novo Nordisk, R. Wu Employee of: Novo Nordisk, K. Valliant-Saunders Employee of: Novo Nordisk, P. Smith Employee of: Novo Nordisk, S. Peng: None Declared, H. Blumberg Employee of: Novo Nordisk, S. Levin Employee of: Novo Nordisk, D. Lundsgaard Employee of: Novo Nordisk